2015
DOI: 10.1016/j.bbrc.2015.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the fusion core in zebrafish endogenous retroviral envelope protein

Abstract: Zebrafish endogenous retrovirus (ZFERV) is the unique endogenous retrovirus in zebrafish, as yet, containing intact open reading frames of its envelope protein gene in zebrafish genome. Similarly, several envelope proteins of endogenous retroviruses in human and other mammalian animal genomes (such as syncytin-1 and 2 in human, syncytin-A and B in mouse) were identified and shown to be functional in induction of cell-cell fusion involved in placental development. ZFERV envelope protein (Env) gene appears to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In recent studies, we found that zebrafish endogenous retrovirus (ZFERV) has an envelope protein gene that maintains a complete open reading frame. This protein is highly expressed in the thymus of zebrafish and has a certain degree of presence in other organizations [ 57 , 58 ]. After exposure to hypoxia, the zebrafish repeat element expression regulation state, especially SSU-rRNA (Hsa), is changed.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, we found that zebrafish endogenous retrovirus (ZFERV) has an envelope protein gene that maintains a complete open reading frame. This protein is highly expressed in the thymus of zebrafish and has a certain degree of presence in other organizations [ 57 , 58 ]. After exposure to hypoxia, the zebrafish repeat element expression regulation state, especially SSU-rRNA (Hsa), is changed.…”
Section: Discussionmentioning
confidence: 99%
“…ZFERV is amplified in zebrafish T-cell leukemia ( Frazer et al, 2012 ). The fusion core of the ZFERV envelope protein has been characterized at the functional level ( Shi et al, 2015 ). In addition to ZFERV-related elements, we could detect two additional families of Epsilon-like sequences in the zebrafish genome that clearly segregate in a phylogeny, indicating the presence of divergent ERVs in this fish ( Figure 2 ).…”
Section: Fish Endogenous Retrovirusesmentioning
confidence: 99%
“…Although a substantial number of RVs-GTE (retroviruses with a gamma-type Env) have been identified across the evolutionary history of vertebrates [15,[17][18][19], these retroviruses in anamniote vertebrates remain poorly understood. Hence, in this study, .…”
Section: Introductionmentioning
confidence: 99%
“…Although a substantial number of RVs-GTE (retroviruses with a gamma-type Env) have been identified across the evolutionary history of vertebrates [15,[17][18][19], these retroviruses in anamniote vertebrates remain poorly understood. Hence, in this study, by incorporating genomic and transcriptomic data and performing comprehensive phylogenomic analyses, we were able to identify hundreds of RV-GTE lineages, which significantly increased the known set of RVs-GTE in anamniote vertebrates.…”
Section: Introductionmentioning
confidence: 99%